2012
DOI: 10.1007/s00246-012-0346-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Analysis of the NKX2-5 Gene Promoter in Patients With Ventricular Septal Defects

Abstract: The ventricular septal defect (VSD) is the most common type of congenital heart disease (CHD). The morbidity and mortality of CHD patients are significantly higher due to late cardiac complications, likely caused by genetic defects. Mutations in cardiac transcription factor genes such as GATA-4, TBX5, and NKX2-5 have been implicated in CHD cases. The NKX2-5 gene, a homeobox gene, is expressed in the developing heart and the adult heart. Because NKX2-5 is a dosage-sensitive regulator during embryonic developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…NKX2.5, a homeodomain transcription factor, is vital in early cardiogenesis in mammals [91]. Mutations in NKX2.5 have been reported in patients with ventral septal defect [92], tetralogy of Fallot, transposition of greater vessels, and patent ductus arteriosus [93], atrial septal defect and hypoplastic left heart syndrome (HLHS) [94]. The association of mutations with clinical manifestations is of paramount importance; NKX2.5 mutation associated ASD was found to present with cardiac conduction defects; thus, patients with mutation in NKX2.5 have an increased risk of cardiac arrest [95].…”
Section: Embryogenesis Of the Heartmentioning
confidence: 99%
“…NKX2.5, a homeodomain transcription factor, is vital in early cardiogenesis in mammals [91]. Mutations in NKX2.5 have been reported in patients with ventral septal defect [92], tetralogy of Fallot, transposition of greater vessels, and patent ductus arteriosus [93], atrial septal defect and hypoplastic left heart syndrome (HLHS) [94]. The association of mutations with clinical manifestations is of paramount importance; NKX2.5 mutation associated ASD was found to present with cardiac conduction defects; thus, patients with mutation in NKX2.5 have an increased risk of cardiac arrest [95].…”
Section: Embryogenesis Of the Heartmentioning
confidence: 99%
“…Seven publications were further excluded after review of the full texts because of the following reasons: the cases in the study by Ouyang et al suffered from coronary artery disease (CAD) and rheumatic heart disease (RHD) [38]; two studies carried out in non-Chinese populations, plus one of which extracted DNA from formalin fixed tissue samples [26], [39]; no complete allele data obtained in other four studies [18], [40], [41], [42]. Finally, 7 studies containing 1243 cases and 1139 controls were relevant to 63A>G and 4 studies containing 748 cases and 630 controls were relevant to 606G>C. Of these studies, 3 studies just explored a single type of CHD [28], [29], [33], whereas multiple types of CHD were involved in the other studies [27], [30], [31], [32]. A same set of control was applied across two studies by Liu et al [28], [29].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the variant was also identified by Reamon-Buettner et al in the diseased heart tissues of 68 patients with CHD by direct sequencing, but the difference in allele frequency was insignificant between CHD cases and healthy controls [26]. However, Shi et al observed significant association in 110 case-control pairs of Chinese [27], which was followed by a number of studies trying to replicate the attractive result in the Chinese population, but with inconsistent findings [28]–[33]. Another synonymous variant 606G>C (rs3729753, Leu202Leu) located in the exon 2 of NKX2-5 , was also suspected to implicate in CHD risk in the Chinese population.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly though, the findings of published studies that used targeted gene panels or exome sequencing implicate that approximately 90% of sporadic CHD patients do not carry mutations in exon regions ( Blue et al, 2017 ), indicating that other causes including unknown pathogenic genes and variations in regulatory regions, should not be ignored. Indeed, mutations in the regulatory regions of cardiac genes can also cause several heart defects ( Pang et al, 2012 ; Smemo et al, 2012 ; Wu et al, 2012 ; Gu et al, 2017 ), such as the mutation rs118026695 within the promoter of NKX2.5 and the homozygous mutation in an enhancer, which is located approximately 90 kb downstream of TBX5. In this study, we found that an enhancer located 84 kb upstream of tnni1b was capable of mediating specific GFP expression in zebrafish hearts.…”
Section: Discussionmentioning
confidence: 99%